Bimbingan Teknis Transformasi Media Promosi pada UD. Rizky Amalia Berbasis Digital Marketing - Andi Dian Sry Rezki Natsir; Fitri Junianti; Rianti Indah Lestari; Riskawati . (Faculty of Engineering UNHAS, 2024)
Community Service is one of the main elements of the Tri Dharma of Higher Education which is the main duty as lecturer including at the ATI Makassar Polytechnic. This Community Service Activity was carried out in the third week of August 2023 and took place at UD. Rizky Amalia, Enrekang Regency. Activities involving owners, mployees of UD Rizky Amalia and several business owners in Buntu Sarong Village. The purpose of implementing the service activity was providing technical guidance on making promotional media by using Artificial Intelligent (AI). The method for measuring the success of activities was carried out by measuring participants' knowledge using pre-test and post-test questionnaires. The average score of the pre-test results was 5.50 before the material and training were given. The post-test average score was 17.50. The increase in the average score for these two groups of respondents indicates the initial assumption that respondents gained increased knowledge from this activity. This is also supported by the results of the paired t test where it is hypothesized that there is an average difference between the pre-test data and the post-test data which shows that there is an influence of providing materials and training on increasing respondents' understanding. This is proven by the significant value of less than 0.05 which was 0.00.